THE PAST AND THE PRESENT OF TOXICOLOGICAL CHEMISTRY. IMPROVING OF TEACHING TOXICOLOGICAL CHEMISTRY ON THE CHAIR OF PHARMACEUTICAL AND TOXICOLOGICAL CHEMISTRY OF THE FIRST MSMU NAMED AFTER I.M. SECHENOV - N. I. Kuznetsova; G. V. Ramenskaya (Сеченовский вестник)
This article provides a brief outline of the history and teaching of the discipline "Toxicological Chemistry" on the chair of pharmaceutical and toxicological chemistry of the First MSMU named after M.I. Sechenov.